Global Lessons Learned for Urban Resilience and Regeneration Projects : Informing Turkey’s Urban Transformation Process - World Bank (World Bank, Washington, DC, 2021)
Over the last decade, turkey has initiated several regulatory and institutional reforms to better mitigate and reduce disaster risks, with a focus on seismic risk. The Squatter (Gecekondu) Law No. 775 (1966) was the first regulatory effort to produce housing for low-income groups in Turkey, and with the Mass Housing Law No. 2985 (1984), they aimed to accelerate the production of social housing. These regulations, which are still in force, demonstrate the importance given to low-income housing production in Turkey. In the 2000s, the legal concept of "urban transformation" emerged; and it started to be mentioned together with "disaster risk". Since 2005, three regulations have informed urban transformation efforts, including the renewal of dilapidated buildings: The 73rd article of the “Municipal Law (2005)” numbered 5393 provides the legal basis for local administrations to carry out urban transformation practices; More precise planning and implementation tools were defined to support the renewal of historical heritage sites, and put under legal provision separately from other urban areas, under the Law No. 5366 on the "the Conservation by Renovation and Use by Renewal of Dilapidated Historical and Cultural Immovable Properties" / "Renewal Act (2005)"; and The "Law on Transformation of Areas Under Disaster Risk" numbered 6306, aimed to increase the resilience of cities against disasters by eliminating the risk in order to ensure the safety of life and property, especially earthquake disasters.